2019
DOI: 10.1155/2019/6976394
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Herbal Formula Shenzhu Tiaopi Granule Results in Metabolic Improvement in Type 2 Diabetic Rats by Modulating the Gut Microbiota

Abstract: Objective. The aim of this study is to investigate the implication of the Chinese herbal formula (CHF) Shenzhu tiaopi Granule (STG) in type 2 diabetes mellitus (T2DM) and discuss the mechanisms by which STG regulates the gut microbiota. Method. Goto-Kakizaki (GK) rats and age-matched Wistar (W) rats were acclimatized for 1 week. The GK rats were randomly divided into 3 groups and orally gavaged with saline (model group, M), acarbose (acarbose group, A), and STG (granule of CHF group, G; the component of this f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Of 47 rodent studies, 30 (63.8%) studies were conducted in mice ( 35 41 , 44 46 , 48 , 52 , 53 , 55 , 56 , 59 65 , 68 , 70 , 74 79 ) and the others were in rats ( 5 , 6 , 42 , 43 , 47 , 49 51 , 54 , 57 , 58 , 66 , 67 , 69 , 71 73 ). Their characteristics, housing, acclimatization, and diet treatments were presented in Table 3 and Supplementary Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 47 rodent studies, 30 (63.8%) studies were conducted in mice ( 35 41 , 44 46 , 48 , 52 , 53 , 55 , 56 , 59 65 , 68 , 70 , 74 79 ) and the others were in rats ( 5 , 6 , 42 , 43 , 47 , 49 51 , 54 , 57 , 58 , 66 , 67 , 69 , 71 73 ). Their characteristics, housing, acclimatization, and diet treatments were presented in Table 3 and Supplementary Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Responses of the phylum Bacteroidetes to different antihyperglycemic agents were investigated in 15 rodent studies. No difference was noted in studies treated with acarbose (5,58). Five out of the seven studies on the genus Bacteroides after using metformin (37,42,48,54,56) revealed increased abundance of this genus in mice and rats.…”
Section: Bacterial Taxamentioning
confidence: 91%
See 2 more Smart Citations
“…In the future, the sample size will be increased for in-depth verification of the findings to improve clinical evidence and to better guide clinical practice. The mechanism of action of these CHM prescriptions can also be further explored [ 50 ].…”
Section: Discussionmentioning
confidence: 99%